PRZEMIANY STRUKTURALNE WŁADZ LOKALNYCH W POLSCE W II POŁOWIE XX WIEKU - Sokalska, Edyta (Zeszyty Prawnicze, 2016)
STRUCTURAL CHANGES IN THE POLISH LOCAL ADMINISTRATIVE BOARDS IN THE SECOND PART OF THE 20TH CENTURY Summary The structural changes of the local administrative boards in Poland in the second half of XX century are the subject of the present study. Mainly legislative bases of functioning and organization of local administrative boards in the period of 1972-1975 are taken into account. During that time the central political authorities were trying to undertake some changes in the local governing. Legislative acts of the great importance were acts of 1972 and 1975 that imposed a new administrative division. The act of 1973 changed some competence of the Polish administrative organs by introducing new ones. The second part of the study shows the new movements in development of the Polish local administrative boards after 1975. During the great transformations of the 1990-ties setting up real local government was one of the most important political decisions. It was return to the concept of the dualistic model of the local administration.